2020
DOI: 10.1128/jvi.00086-20
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Determinant of West Nile Virus Secretion and Morphology as a Target for Viral Attenuation

Abstract: West Nile virus (WNV), a member of the Flavivirus genus and currently one of the most common arboviruses worldwide, is associated with severe neurological disease in humans. Its high potential to reemerge and rapidly disseminate makes it a bona fide global public health problem. The surface membrane glycoprotein (M) has been associated with Flavivirus-induced pathogenesis. Here, we identified a key amino acid residue at position 36 of the M protein whose mutation impacts WNV secretion and promotes viral attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
(47 reference statements)
1
16
0
Order By: Relevance
“…The table details residues involved in virulence variation in vivo and in vitro and shared by at least two flaviviruses. TBEV: tick-borne encephalitis virus; DENV: dengue virus; ZIKV: zika virus; YFV yellow fever virus; JEV: Japanese encephalitis virus; MVEV: Murray valley encephalitis virus [92,97,99,102,[106][107][108]112,113,116,177,. [112,116,187,190] DENV G102S, F108A [191] Domain III (receptor binding site) JEV E306K…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The table details residues involved in virulence variation in vivo and in vitro and shared by at least two flaviviruses. TBEV: tick-borne encephalitis virus; DENV: dengue virus; ZIKV: zika virus; YFV yellow fever virus; JEV: Japanese encephalitis virus; MVEV: Murray valley encephalitis virus [92,97,99,102,[106][107][108]112,113,116,177,. [112,116,187,190] DENV G102S, F108A [191] Domain III (receptor binding site) JEV E306K…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that mutations in the protein M could produce attenuated flaviviruses, such as JEV [96]. A recent study of Basset et al [97] investigated the effect of protein M mutation in WNV. The authors generated WNV mutants by PCR from an IC of WNV Israel 98 (IS98) [3], which is genetically closely related to the NY99 strain.…”
Section: Prm Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiments have confirmed that a vaccine derived from a chimeric virus, which was constructed using the structural proteins (M and E) of the Kunjin WNV strain and the genome backbone of the insect-specific Binjari virus, offered efficient protection against virulent WNV strains, including the highly pathogenic WNV NY 99 strain ( Vet et al, 2020 ). In the WNV, the structural proteins E and M are responsible for binding to receptors, e.g., the dendritic cell- and liver/lymph node-specific intercellular adhesion molecule-3-grabbing non-integrins (DC-SIGN and L-SIGN, respectively), and have been associated with flavivirus-induced pathogenesis ( Khoo et al, 2008 ; Basset et al, 2020 ). Hence, their function in the WNV is to some extent similar to the function of the spike (S) protein of SARS-CoV-2 ( Huang et al, 2020 ).…”
Section: Flaviviruses (Family Flaviviridae )mentioning
confidence: 99%
“…A common strategy for obtaining a live vaccine is to pass the isolated wild strains in serial passages to generate attenuated strains with mutations in certain residues, and the attenuated strains are candidates for vaccines [ 71 , 72 ]. Usually, attenuated strains will differ from the wild type in many ways, for example, by influencing the secretion of the virus and decreasing viremia levels and the efficiency of replication in major target organs [ 60 , 73 ]. JEV attenuated strain SA14-14–2 (JEV SA14-14–2) is a vaccine strain with good protection effectiveness and safety [ 74 , 75 ].…”
Section: The Key Amino Acids Of the E Protein Involved In Flavivirus Early Infectionmentioning
confidence: 99%